The Relationship between SLC22A16 Gene Polymorphism and Hematological Toxicity in Breast Cancer Patients Receiving Doxorubicin-Based Chemotherapy - KABAN, SRI MELINDA; Siti Syarifah; Pane, Yunita Sari; Tri Widyawati (TALENTA Publisher, Universitas Sumatera Utara, 2025)
ABSTRACT Background Drug transporter polymorphisms are widely associated with the risk of toxicity in many chemotherapy drugs in cancer. This paper aims to assess the relationship of polymorphisms of this transporter, namely SLC22A16, which are associated with side effects of Doxorubicin-based chemotherapy drugs, namely hematological toxicity (anemia, neutropenia, leukopenia and thrombocytopenia) in breast cancer patients. Method This cross-sectional study will be conducted by testing polymorphism using the ARMS PCR method, which will assess the distribution of AA, AG, and GG genotypes. Result Most patient ages are under 50 years (55%), with overweight BMI (41,7%) and Batak ethnicity (43,3%). There is no relationship between SLC22A16 Gene Polymorphism and Hematological Toxicity in Breast Cancer Patients Receiving Doxorubicin-Based Chemotherapy